The South Tibetan Detachment and the Manaslu Leucogranite: A structural reinterpretation and restoration of the Annapurna-Manaslu Himalaya, Nepal - Searle, M; Godin, L (2003)
The South Tibetan Detachment (STD) System comprises both ductile shear zones and brittle low-angle extensional faults bounding the upper (northern) margin of the high-grade metamorphic and anatectic rocks of the Greater Himalayan Sequence (GHS). Along the Himalayan chain from Zanskar in the west to Bhutan in the east, leucogranites are restricted to the footwall of the STD and rarely, if ever, intrude across the fault into unmetamorphosed sedimentary rocks of the Tethyan zone. The Manaslu leucogranite (24-19 Ma) was previously thought to be an exception, intruding up as far as the Triassic sediments. We have mapped a newly discovered 350-400-m-thick shear zone of high-strain mylonites along the upper Nar Valley and Pangre glacier (Phu Detachment = STD), west of the Manaslu-Himlung massif, which wraps around the northern (upper) margin of the Manaslu leucogranite. All rocks beneath the Manaslu leucogranite are metamorphosed, and no leucogranites intrude across this shear zone, in common with observations elsewhere along the Himalaya. The age of motion along the STD in the Manaslu region is constrained as being younger than 18 Ma, not older than 24 Ma as previously thought. The Chame Detachment (CD) is a ductile shear zone wholly within the GHS. Pressure-temperature conditions of diopside + K-feldspar + tremolite marbles and calc-silicates, and sillimanite ± kyanite meta-pelites above the CD are similar to conditions for calc-silicates, pelites, and augen gneisses below. We have used structural data and PT constraints in conjunction with stratigraphy to restore the entire GHS in the Annapurna-Manaslu region, prior to the Early Miocene formation of the Manaslu leucogranite and the STD System of normal faults. These Miocene faults and shear zones cut across the earlier Oligocene north-verging folds exposed in the Annapurna range. Ductile shearing along upper levels of the Main Central Thrust zone and along the CD occurred before 21 Ma, and brittle faulting along the STD occurred after 19-18 Ma. Rapid exhumation and cooling of the GHS and Manaslu granite between 18 and 15 Ma was followed by initiation of east-west extension in the Thakkhola Graben north of the STD and propagation of thrusting southward into the Lesser Himalaya.